Kre6 (yeast 1,6-β-transglycosylase) homolog, PhTGS, is essential for β-glucan synthesis in the haptophyte Pleurochrysis haptonemofera - Inukai, Mayuka; Kobayashi, Naoya; Endo, Hirotoshi; Asakawa, Koki; Amano, Keisuke; Yasuda, Yuki; Cenci, Ugo; Colleoni, Christophe; Ball, Steven; Fujiwara, Shoko (Frontiers in Bioengineering and Biotechnology, 2023)
Haptophytes synthesize unique b-glucans containing more b-1,6-linkage than b-1,3 linkage, as a storage polysaccharide. To understand the mechanism of the synthesis, we investigated the roles of Kre6 (yeast 1,6-b-transglycosylase) homolog, PhTGS, in the haptophyte Pleurochrysis haptonemofera. RNAi of PhTGS repressed b-glucan accumulation and simultaneously induced lipid production, suggesting that PhTGS is involved in b-glucan synthesis and the knockdown leads to the alteration of carbon metabolic flow. PhTGS was expressed in light, in which b-glucan was actively produced through photosynthesis, more than in the dark. Crude extract of E. coli expressing PhKre6 demonstrated its activity to incorporate 14 C-UDP-glucose into b-glucan of Pleurochrysis. These findings suggest that PhTGS functions in storage b-glucan synthesis mainly in light, probably by producing b-1,6-branch.